Photonic bandgap engineering using second-order supersymmetry - Nitish Chandra (Nature Portfolio, 2021)
Supersymmetric (SUSY) transformations, which originated in quantum physics offer a robust, physics-based approach to design photonic structures. The authors apply second-order SUSY to engineer non-uniform surface corrugation of waveguide gratings and coupling potential, and its application in photonics.